Anaesthesia management of a patient in MRT (Magnetic Resonance Tomography). Save working environment – it must be achieved - Bilskienė, Diana; Macas, Andrius (Acta medica Lituanica, 2012)
Magnetic resonance imaging (MRI) provides specific diagnostic information that cannot be obtained by other methods: computed tomography, ultrasound and others. Movements during the MRI examination cause artifacts, therefore patients must remain motionless during the entire study period. Anaesthesia during the MRI examination is a way to ensure the quality of investigations. Some patients, children and adults with movement and learning disorders or claustrophobia, are unable to lie still during the MRI scan and consequently sedation or general anaesthesia is required. The continuous presence of a strong magnetic field and restricted access to the patient means that the provision of anaesthesia within MR units presents unique problems. General anaesthesia for paediatric patients undergoing MRI is a safe and effective method in the MRI room with special anaesthesia equipment. Therefore, general anaesthesia is often indicated to increase safety, to improve the quality of imaging, to increase the comfort of patients and for the improvement of logistics of the MRI suite. The safety of the procedure is defined by the possibility of having equipment, monitoring and qualified staff.
Keywords: magnetic resonance imaging (MRI); general anaesthesia; safety; special anaesthesia equipment; comfort; qualified staff